A Case Report on Aicardi-Goutieres Syndrome 7 - Alexander, Sherin (Indian Journal of Pharmacy Practice)
Aicardi-Goutieres Syndrome (AGS) is a genetically heterogeneous neurodevelopmental disorder which most typically affects brain and skin. It is an inflammatory disorder resulting from mutation of the genes. Majority of the affected individuals experiences physical as well as intellectual problems. Here we discuss a case of Aicardi- Goutieres Syndrome 7. And in our case, this syndrome is due to the mutation of IFIH1 gene.
Keywords: AicardiGoutieres Syndrome; IFIH; Gene mutation; Neurodevelopmental disorder; Inflammatory disorder.